Neonatal pain assessment: Do we have the right tools? - Llerena, Amelia; Tran, Krystal; Choudhary, Danyal; Hausmann, Jacqueline; Goldgof, Dmitry; Sun, Yu; Prescott, Stephanie M. (Frontiers in Pediatrics, 2023)
Background The assessment and management of neonatal pain is crucial for the development and wellbeing of vulnerable infants. Specifically, neonatal pain is associated with adverse health outcomes but is often under-identified and therefore under-treated. Neonatal stress may be misinterpreted as pain and may therefore be treated inappropriately. The assessment of neonatal pain is complicated by the non-verbal status of patients, age-dependent variation in pain responses, limited education on identifying pain in premature infants, and the clinical utility of existing tools. Objective We review research surrounding neonatal pain assessment scales currently in use to assess neonatal pain in the neonatal intensive care unit. Methods We performed a systematic review of original research using PRISMA guidelines for literature published between 2016 and 2021 using the key words “neonatal pain assessment” in the databases Web of Science, PubMed, and CINAHL. Fifteen articles remained after review, duplicate, irrelevant, or low-quality articles were eliminated. Results We found research evaluating 13 neonatal pain scales. Important measurement categories include behavioral parameters, physiological parameters, continuous pain, acute pain, chronic pain, and the ability to distinguish between pain and stress. Provider education, inter-rater reliability and ease of use are important factors that contribute to an assessment tool's success. Each scale studied had strengths and limitations that aided or hindered its use for measuring neonatal pain in the neonatal intensive care unit, but no scale excelled in all areas identified as important for reliably identifying and measuring pain in this vulnerable population. Conclusion A more comprehensive neonatal pain assessment tool and more provider education on differences in pain signals in premature neonates may be needed to increase the clinical utility of pain scales that address the different aspects of neonatal pain.